ANALYSIS OF BIOCOMPATIBILITY OF MATERIALS FOR NON-REMOVABLE AESTHETIC PROSTHETIC STRUCTURES - P.Z. Ozhohan; Z.R. Ozhogan (Український стоматологічний альманах, 2024)
Background. Currently, zirconium dioxide and metal-free ceramics are widely used in orthopedic dentistry. Studying the surfaces of these materials at the microand nanoscale is becoming increasingly important in dental research, allowing us to uncover the complex interactions between dental materials and oral tissues. Atomic force microscopy allows us to study the influence of microand nanoscale features of the surface of materials on bacterial adhesion, biofilm formation, and osseointegration processes. Contact angle analysis characterizes surface energy and hydrophobicity, which are the basis for models of protein adsorption, cell adhesion, and interaction of oral fluid with the surface of the teeth. Such studies prove the effect of wetting dental materials on their interaction with oral fluid, blood, and other biological fluids in the oral cavity.